2015
DOI: 10.1177/1753425915572172
|View full text |Cite
|
Sign up to set email alerts
|

Elevated matrix metalloproteinase-8 in saliva and serum in polycystic ovary syndrome and association with gingival inflammation

Abstract: This study aimed to investigate the levels of matrix metalloproteinase-8 (MMP-8) and tissue inhibitors of MMP-1 (TIMP-1) in saliva and serum samples of women with polycystic ovary syndrome (PCOS; n = 80) and matched systemically healthy controls (n = 45), with varying degrees of gingival inflammation. Salivary levels of MMP-8 and the MMP-8/TIMP-1 ratio were significantly elevated in women with PCOS, who also exhibited more gingivitis than systemically healthy women. No major changes were observed in salivary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
(68 reference statements)
2
37
1
2
Order By: Relevance
“…Also, inflammatory biomarker levels associated with oral diseases would be diluted in serum compared with saliva. 6,47 In line with that, higher concentrations of molecules analyzed in saliva compared with serum were observed, with the exception of MIF, which was higher in serum.…”
Section: Variablessupporting
confidence: 77%
“…Also, inflammatory biomarker levels associated with oral diseases would be diluted in serum compared with saliva. 6,47 In line with that, higher concentrations of molecules analyzed in saliva compared with serum were observed, with the exception of MIF, which was higher in serum.…”
Section: Variablessupporting
confidence: 77%
“…Biomarkers and their combinations or cascades reflecting oral inflammation could thus supplement clinical oral examination or even serve as screening tools . Saliva contains many potential biomarkers, such as sTREM‐1; IL‐1β, −6, and −8; TNF‐α; MMP‐8 and ‐9; and TIMP‐1, and could thus indeed be used for screening, diagnosing, tracking, and predicting different oral and systemic diseases . Because biologic fluids are not stationary but circulatory, salivary MMP‐8 and sTREM‐1 levels may reflect not only oral but also systemic inflammatory diseases, like endocrine gynecologic disorders and cardiovascular diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Saliva contains many potential biomarkers, such as sTREM‐1; IL‐1β, −6, and −8; TNF‐α; MMP‐8 and ‐9; and TIMP‐1, and could thus indeed be used for screening, diagnosing, tracking, and predicting different oral and systemic diseases . Because biologic fluids are not stationary but circulatory, salivary MMP‐8 and sTREM‐1 levels may reflect not only oral but also systemic inflammatory diseases, like endocrine gynecologic disorders and cardiovascular diseases . Such point‐of‐care or chairside lateral flow immunotests are already commercially available and validated with different age groups and ethnic backgrounds for MMP‐8 .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have evaluated the relationship between PCOS and periodontal diseases, all of which found that individuals with PCOS seem to be more prone to gingival inflammation. This may be related to the role of chronic systemic inflammation in the pathophysiology of both PCOS and periodontal disease …”
Section: Discussionmentioning
confidence: 99%